Penurunan Derajat Kejenuhan Simpang Tak Bersinyal 15 Tahun Menggunakan PKJI 2023 dan PTV VISSIM - Daffa Nugraha; Athaya Zhafirah; Greece Maria Lawalata (Institut Teknologi Garut, 2026)
Intersections involve continuous and crossing traffic movements, creating potential conflicts that require traffic control. This study aims to evaluate the performance of the Letjen Ibrahim Adjie–Rancabango unsignalized intersection in Tarogong Kaler District, Garut Regency, over the next 15 years and to address traffic problems at the location. The method includes the collection of primary data through vehicle volume surveys, road geometric data, as well as vehicle travel time and speed. The data were analyzed using the Indonesian Highway Capacity Guidelines (PKJI 2023). Secondary data consist of literature reviews related to the implementation of traffic management at intersections in other locations. Traffic performance modeling and evaluation were conducted using PTV Vissim Student Version simulation software. The analysis results show an intersection capacity of 2,880 pcu/hour during peak hours, with a Degree of Saturation (DS) of 0.97, classified as Level of Service E (stable flow with high interference), and an average delay of 13.89 seconds/pcu. PTV Vissim simulation recorded a vehicle volume of 279 vehicles and an average delay of 14.39 seconds/vehicle. One of the implemented solutions was a right-turn prohibition to reduce the degree of saturation and traffic delay. After implementation, the Degree of Saturation decreased to 0.74 (Level of Service C, more stable flow) with a delay of 8.41 seconds/pcu. The simulated vehicle volume was 230.5 vehicles with an average delay of 8.27 seconds/vehicle, indicating improved intersection performance. This study contributes technical recommendations that can serve as a basis for urban transportation planning and support traffic management policies in developing areas such as Garut Regency.